The Effectiveness of Technology Integration by Redefinition in Teaching Asian History among Grade 7 Learners in a Catholic School - Alison, Angelica V.; Dioso, Dexter Paul D. (Philippine Social Science Journal, 2025)
This quasi-experimental study evaluated the effectiveness of integrating technology at the "Redefinition" level of the SAMR model in teaching Asian History to 160 Grade 7 students at a Catholic school. Analysis of pre-test and post-test data revealed that employing this high level of technology integration significantly enhanced student academic achievement and performance. Supported by the TPACK framework, these findings underscore the transformative potential of the Redefinition level in fostering engagement, critical thinking, and digital literacy through novel, interactive learning experiences. To build upon these insights, future research should utilize larger, more diverse samples and investigate interventions across all SAMR levels to fully understand the scaffolding required for effective technological progression.